SALINIZATION PROCESSES IN AN ALLUVIAL COASTAL LOWLAND PLAIN AND EFFECT OF SEA WATER LEVEL RISE - Don N.C.; Hang N.T.M.; Araki H.; Yamanishi H.; Koga K. (My University, 2006)
In coastal areas, groundwater and aquifer systems are easily prone to pollution and contamination. Moreover, sea level rises also threaten the viability of many coastal zones and small islands. In the Shiroishi lowland plain, southwestern Kyushu Island of Japan, some environmental problems such as land subsidence and salinity intrusion due to over pumping of groundwater have long been recognized as water problems and become causes for public concern. In this study, an integrated surface and groundwater model was established and applied to the Shiroishi site to simulate groundwater flow hydraulics and predict the salinity intrusion process in the alluvial lowland plain. The simulated results show that groundwater levels in the aquifer greatly vary in response to varying climatic and pumping conditions. It is also found that sea water intrusion would be expected along the coast if the current rates of groundwater exploitation continue. Furthermore, sea water intrusion with a relative rise in sea water level due to aquifer compression and global climatic change was also considered. As a result, sea water intrusion appears to extend much farther in land from the coast compared to a reference case. The study also suggests a possible alternative to mitigate the inverse effects by pumping groundwater.
Keywords: COASTAL LOWLAND PLAIN; GROUNDWATER OVER-WITHDRAWAL; INTEGRATED SURFACE AND GROUNDWATER MODELING; SALINITY ENCROACHMENT; RELATIVE SEA WATER LEVEL RISE; SHIROISHI PLAIN; KYUSHU ISLAND; JAPAN